PENGARUH PENGUNGKAPAN LAPORAN KEBERLANJUTAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN DI INDONESIA - Nurhalim Gaffar Ronaldo; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of the disclosure of sustainability reports on the financial performance of banking companies in Indonesia. The independent variabels used are sustainability reporting in aggregate, disclosure of the economic dimension, disclosure of environmental dimension, and the disclosure of social dimension. The dependent variable in this study is financial performance as measured using ROA. The hypothesis put forward in this study is the influence of sustainability reports in aggregate, disclosure of economic dimension, disclosure of environmental dimension, and disclosure of social dimension to the company’s financial performance. This research used samples from 69 GRI-standar sustainability reports consisting of 32 banking companies listed in the Indonesia Stock Exchange in the period 2020 to 2022. The data used in this research is secondary data and the sample taken with purposive judgment sampling method. In testing the hypothesis, this study uses multiple and simple linear regression analysis. The results of this research indicate that only disclosure of sustainability report in aggregate and the disclosure of the economic dimension affects the financial performance of banking companies as measured using ROA, while disclosure of the environmental dimension, and disclosure of the social dimension do not affect the financial performance of banking companies as measured using ROA. Thus, it can be concluded that only disclosure of sustainability reports in aggregate and disclosure of economic dimension affects the financial performance of banking companies.